(untitled) (American Journal of Management, 2017)
McDonalds restaurants began offering a limited breakfast menu all day in October of 2015 to catalyze business growth. This decision was made in a time when eggs were in shortage due to the outbreak of highly pathogenic avian influenza (HPAI) in U.S. poultry. The outbreak led to a limited supply of layer birds, and led to higher retail prices through direct and indirect consumption. Using a partial equilibrium model of U.S. layer flocks, welfare impacts of an increase in demand coupled with a decrease in supply were estimated and shown to slightly drive up the price of retail table egg.